PENGARUH PEMBERIAN PROBIOTIK DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN BENIH IKAN BANDENG (Chanos chanos FORKSAL) - Ayuda Septiana M; Muhamad Agus; Hadi Pranggono (Fakultas Perikanan Universitas Pekalongan, 2017)
Milkfish is one commodity that has high economic value because it is important in the fulfillment of community nutrition. This study aims to determine the provision of probiotics from banana stumps, with different doses in artificial feed on the growth of milkfish seed (Chanos chanos Forskal). The study used a completely randomized design with 4 treatments and 3 replications. The treatments were 3 cc / kg of feed, 6 cc / kg of feed, 9 cc / kg of feed and 12 cc / kg of feed. The research was conducted from 23rd May – 21st June 2015 at the Brackish Water Laboratory of Slamaran. The results showed that the highest average biomass growth in the treatment of doses of 12 cc / kg of feed reached 14.75 grams. The lowest yield was obtained in the treatment of 3 cc / kg of feed about 10.00 grams. The growth response to the proportional dose rate showed a linear form and the survival rate of larvae reached 100%. The water quality range during research is still appropriate to support growth, where temperatures range from 23 to 31 C. pH ranges from 6.5 to 7.5, dissolved oxygen content ranges from 5.5 to 5.6 ppm and salinity of 8-12 ppt.Key Word : Probiotics, growth, Milkfish